2021
DOI: 10.3847/2041-8213/abde36
|View full text |Cite
|
Sign up to set email alerts
|

On the Synthesis of the Astronomically Elusive 1-Ethynyl-3-Silacyclopropenylidene (c-SiC4H2) Molecule in Circumstellar Envelopes of Carbon-rich Asymptotic Giant Branch Stars and Its Potential Role in the Formation of the Silicon Tetracarbide Chain (SiC4)

Abstract: Organosilicon molecules such as silicon carbide (SiC), silicon dicarbide (c-SiC2), silicon tricarbide (c-SiC3), and silicon tetracarbide (SiC4) represent basic molecular building blocks connected to the growth of silicon-carbide dust grains in the outflow of circumstellar envelopes of carbon-rich asymptotic giant branch (AGB) stars. Yet, the fundamental mechanisms of the formation of silicon carbides and of the early processes that initiate the coupling of silicon–carbon bonds in circumstellar envelopes have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The astronomical detection of silicon carbides (SiC, c-SiC 2 , c-SiC 3 , and SiC 4 ) 33 along with silane (SiH 4 ) 34 and methylsilane (CH 3 SiH 3 ) 35 toward IRC+10216 documents a striking gas-phase chemistry, whose initial silicon−carbon bond formation mechanisms are only beginning to emerge. 36 The prospective identification of hydrogenated silicon−carbon clusters such as singlet ethynylsilylene via rotational spectroscopy exploiting the Atacama Large Millimeter/submillimeter Array would exploit circumstellar envelopes as natural laboratories for an exotic silicon− carbon chemistry under extreme conditions. This would provide an opportunity to identify fundamental elementary reactions leading to silicon−carbon bond formation in deep space by guiding astronomical observations with both laboratory experiments under single-collision conditions and theoretical investigations.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
See 1 more Smart Citation
“…The astronomical detection of silicon carbides (SiC, c-SiC 2 , c-SiC 3 , and SiC 4 ) 33 along with silane (SiH 4 ) 34 and methylsilane (CH 3 SiH 3 ) 35 toward IRC+10216 documents a striking gas-phase chemistry, whose initial silicon−carbon bond formation mechanisms are only beginning to emerge. 36 The prospective identification of hydrogenated silicon−carbon clusters such as singlet ethynylsilylene via rotational spectroscopy exploiting the Atacama Large Millimeter/submillimeter Array would exploit circumstellar envelopes as natural laboratories for an exotic silicon− carbon chemistry under extreme conditions. This would provide an opportunity to identify fundamental elementary reactions leading to silicon−carbon bond formation in deep space by guiding astronomical observations with both laboratory experiments under single-collision conditions and theoretical investigations.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
“…The facile preparation and identification of gas-phase singlet ethynylsilylene (HCCSiH; p3 ; 1 A′) also has significant implications for the chemistry in circumstellar environments of carbon-rich asymptotic giant branch (AGB) stars such as IRC+10216. The astronomical detection of silicon carbides (SiC, c-SiC 2 , c-SiC 3 , and SiC 4 ) along with silane (SiH 4 ) and methylsilane (CH 3 SiH 3 ) toward IRC+10216 documents a striking gas-phase chemistry, whose initial silicon–carbon bond formation mechanisms are only beginning to emerge . The prospective identification of hydrogenated silicon–carbon clusters such as singlet ethynylsilylene via rotational spectroscopy exploiting the Atacama Large Millimeter/submillimeter Array would exploit circumstellar envelopes as natural laboratories for an exotic silicon–carbon chemistry under extreme conditions.…”
mentioning
confidence: 99%
“…Following the astrophysical detection of c-C 3 HC 2 H (Cernicharo et al 2021), a mechanistic study of its formation found that c-C 3 HC 2 H may form through a gas-phase reaction between c-C 3 H 2 and the ethynyl radical (Fortenberry 2021). These results open a veritable Pandora's box for further astrochemical analysis regarding the formation of c-C 3 H 2 and its family of derivatives (He et al 2022;Yang et al 2021).…”
Section: Introductionmentioning
confidence: 94%
“…35,36 Owing to this reason, the chemistry of organosilicon compounds is considered a fundamental problem in astrochemistry. 34,37,38 In the present work, we have explored the chemical bonding nature of seven low-lying isomers of SiC 4 H 2 , which are 1ethynyl-3-silacycloprop-1(2)-en-3-ylidene (1), diethynylsilylidene (2), 2-methylenesilabicyclo[1.1.0]but-1(3)-en-4-ylidene (3), 1-sila-1,2,3,4-pentatetraenylidene (4), 1,3-butadiynylsilylidene (5), 4-sila-2-methylenebicyclo[1.1.0]but-1(3)-en-4-ylidene (6), and 3-ethynyl-1-silapropadienylidene (7), as depicted with Wiberg bond indices (WBI) in Figure 1 and listed in Table S1. In 1998, Maier and co-workers had trapped 1-ethynyl-3 silacycloprop-1(2)-en-3-ylidene (1) and diethynyl-silylidene (2) experimentally in an Ar matrix at 10 K by flash pyrolysis of triethynylsilane [HSi(C 2 H) 3 ] and 1,1-diethynyl 2,2,2-trimethyldisilane [Me 3 Si−SiH(CCH) 2 ].…”
Section: Introductionmentioning
confidence: 99%